Irish enterprise digitalisation: A cross-country exploration - Hogan, Karen; Kren, Janez; O'Toole, Conor (ESRI, 2024)
This research provides a cross-country perspective on the rate of digitalisation of Irish enterprises. We explore differences across countries, sectors and firm size categories by deploying data on both the usage of digitalisation technologies (stock of digital activities) as well as investment in new digital activities (flow). We draw on two main datasets: a) the Eurostat ICT usage in enterprises survey; and b) the European Investment Bank Investment Survey. We find that Ireland performs relatively well in terms of e-commerce and some more advanced technologies. However particular sectors and firm size groups (such as construction and smaller firms) display low levels of digitalisation. This supports the continued deployment of a sector-specific targeted policy approach that can cater for heterogeneous challenges faced by different firms. We find some evidence of correlations between enabling factors like employment skill levels and the cost of finance and the level of investment in digitalisation.